Assessing prevalence and predictors of impaired awareness of hypoglycemia in type 2 diabetes patients with chronic kidney disease - Amin Soliman; Noran Atef El Kordy; Farouk Mostafa Faris; Rabab Mahmoud Ahmed (The Egyptian Journal of Internal Medicine)
Abstract Background This study aims to determine the prevalence of impaired awareness of hypoglycemia (IAH) across all chronic kidney disease stages in patients with type 2 diabetes mellitus and to identify predictors of impaired awareness of hypoglycemia within these patients. Methods Clinical and laboratory data were extracted from patient medical records. Participants were interviewed using validated modified Clarke’s questionnaire and Gold score to assess impaired awareness of hypoglycemia. Results Cross sectional study included 480 participants diagnosed with chronic kidney disease and type 2 diabetes. The overall prevalence of impaired awareness of hypoglycemia (IAH) was 34.6% (166 patients) according to the Clarke questionnaire and 34.4% by the Gold Score (165 patients). This prevalence varied significantly across different CKD stages, with higher rates in stage 3 (P value = 0.001). The mean impaired awareness of hypoglycemia scores were 3.98 ± 1.34 (Clarke) and 3.92 ± 1.52 (Gold), with advanced CKD stages showing statistically significant elevated scores (p value ≤ 0.05). In the 166 patients with impaired awareness of hypoglycemia, a statistically significant higher incidence of severe hypoglycemia was observed in hemodialysis patients (p value = 0.01). Most of patients with impaired awareness of hypoglycemia aged > 60 years, had more prevalent hypertension and had lower HbA1c levels (P value ≤ 0.05). However, Multivariate logistic regression analysis found that age > 60 years was a significant independent risk factor with an 8% higher risk for IAH (P = 0.01), (OR 1.08, 95% CI 1.01–1.16). Conclusion The present study is unique in investigating impaired awareness of hypoglycemia (IAH) across the full spectrum of chronic kidney disease (CKD) stages, including patients on hemodialysis. Approximately one-third of CKD patients with type 2 diabetes mellitus exhibited a general lack of awareness of hypoglycemia. Patients with stage 3 CKD showed the highest prevalence of IAH. Those already experiencing IAH and receiving hemodialysis faced more severe hypoglycemic episodes. Age over 60 years was an independent risk factor for hypoglycemia unawareness in this patient group. Larger wide scale studies are needed to further validate these results.